Impact of Nuclear Energy on The Environment - Faishal, Faiq; Samputra, Palupi Lindiasari (UI Scholars Hub, 2024)
The purpose of this research is to see what impact nuclear energy has on the environment. The method used is synthesis analysis with a systematic literature review of the data obtained through Google Scholar. This research then makes a review or conclusion based on 20 previous studies that discuss the impact of nuclear energy on the environment. The results showed that nuclear energy had a negative impact on the environment, especially the Chernobyl and Fukushima tragedies. 70% of previous studies explained that nuclear energy has a negative impact on the environment, mainly due to the risk of accidents and the dangers of nuclear fuel waste. Several previous studies have presented mitigations carried out in overcoming the negative impacts of nuclear energy such as health monitoring and increasing safety standards.